(untitled) (Journal of International Studies, 2020)
End of the cold war following the disintegration of the Soviet Union witnessed unprecedented increase in militancy and terrorism prompted by internal and external forces. This was also fuelled by factors like religious fundamentalism and ethno-nationalist chauvinism. The newly independent countries of the Central Asian region encountered myriad problems like terrorism, drug trafficking, arms trafficking, organized crime, separatism, and ethnic conflicts. Given the geographical proximity and historicity, Central Asia is regarded as Russiaâ€™s own backyard and a â€œsoft underbellyâ€. The near-abroad security developments in the Central Asian republics have great influence on Russia and could create a complex environment detrimental to its security interests. The Russian approach to this challenge is of great importance for the stability of the whole area. Any negative developments in Central Asian Regions and Afghanistan would have serious security implications for Russia. A stable and friendly government in Afghanistan and Central Asian states would prove beneficial to Russian security, including the on ongoing separatist movements in Chechnya and Dagestan. Therefore it is imperative that Russia and Central Asian states act collectively to counter religious radicalism and foster regional stability. This article examines some factors responsible for breeding terrorism and religious extremism in Central Asian Republics and its security implications onRussia such as Central Asian threats, US presence in Central Asia and the Taliban in Afghanistan.